1995
DOI: 10.1002/ijc.2910610425
|View full text |Cite
|
Sign up to set email alerts
|

IGF‐2 autocrine stimulation in tumorigenic clones of a human colon‐carcinoma cell line

Abstract: Clonal analysis has shown that the SW613-S human colon-carcinoma cell line is heterogeneous: some cell clones display a high level of amplification of the c-myc gene and are tumorigenic in nude mice, whereas others have a small number of copies of this gene and are non-tumorigenic. Tumorigenic clones can proliferate in a chemically defined serum-free medium, whereas non-tumorigenic clones cannot. Suramin, like anti-insulin-like growth factor (IGF) or anti-IGF-I receptor antibodies, efficiently inhibits the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Harrington et al (1994a) demonstrated that some cytokines, including the IGFs and PDGF, may act as survival factors and block c-myc-induced apoptosis. Previous work on tumorigenic and non-tumorigenic SW613-S-derived clones proved that 12A1 cells overexpress the genes of several growth factors, including PDGF-A and IGF-2, as compared to B3 cells (Galdemard et al, 1995;Lamonerie et al, 1995;Lavialle et al, 1989;Modjtahedi et al, 1992). In addition, it was shown that tumorigenic 12A1 cells can proliferate in a chemically de®ned, serum-free medium containing only transferrin as a proteinaceous component, whereas non-tumorigenic B3 cells cannot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Harrington et al (1994a) demonstrated that some cytokines, including the IGFs and PDGF, may act as survival factors and block c-myc-induced apoptosis. Previous work on tumorigenic and non-tumorigenic SW613-S-derived clones proved that 12A1 cells overexpress the genes of several growth factors, including PDGF-A and IGF-2, as compared to B3 cells (Galdemard et al, 1995;Lamonerie et al, 1995;Lavialle et al, 1989;Modjtahedi et al, 1992). In addition, it was shown that tumorigenic 12A1 cells can proliferate in a chemically de®ned, serum-free medium containing only transferrin as a proteinaceous component, whereas non-tumorigenic B3 cells cannot.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that tumorigenic 12A1 cells can proliferate in a chemically de®ned, serum-free medium containing only transferrin as a proteinaceous component, whereas non-tumorigenic B3 cells cannot. Moreover, we have previously reported that IGF-2 acts through an autocrine pathway that is essential for the growth of tumorigenic cells under these serum-free culture conditions (Lamonerie et al, 1995). Since tumorigenic cells cannot grow in de®ned medium devoid of transferrin and since none of the growth factors overproduced by tumorigenic cells is apparently su cient by itself to suppress c-myc-induced apoptosis in the absence of transferrin, we conclude that transferrin is a likely candidate as a survival factor for these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF II is speculated to serve as an autocrine growth factor in various cancers, because they often coexpress the IGF II and the IGF I receptor. [1][2][3][4] The IGF II gene expression is monoallelic in all the normal tissues other than the liver because of the imprinting of the maternal allele. However, interestingly, most of the cancers arising in these tissues, such as lung cancers, breast cancers, esophageal cancers, Wilms' tumor, and cervical cancers, are reported to show biallelic expression (relaxation) of the IGF II gene.…”
Section: Allelic Imbalance Of the Insulin-like Growth Factor II (Igf mentioning
confidence: 99%
“…This is a potent growth stimulant which is expressed at high levels in colorectal carcinoma, hepatoblastoma, breast cancer, rhabdomyosarcoma, and Wilm's tumor, among other cancer types (Guo et al, 1995;Lamonerie et al, 1995;Rainier et al, 1995;Manni et al, 1994;Minniti et al, 1994;Yun et al, 1993). Furthermore, conditioned media from human colon cancer cell lines contain elevated levels of IGFII prohormone, a more biologically potent form of IGFII (Culouscou et al, 1990).…”
Section: Introductionmentioning
confidence: 99%